Postcolonial Trauma Caused by Dehumanization in Esi Edugyan's Washington Black (2018) - Frianda, Septian; Wahyuni, Delvi (English Language and Literature, 2023)
This analysis explores the issue of Postcolonial trauma caused by dehumanization in the novel "Washington Black" by Esy Edugyan. This analysis is text-based interpretation by applying Franz Fanon's theory of dehumanization can cause Postcolonial trauma. This analysis is to find out how dehumanization can cause Postcolonial trauma to colonized people. The result of this research found several act of dehumanization that makes colonized people feel Postcolonial trauma such as animalistic dehumanization and mechanical dehumanization.